STRUKTUR DAN KOMPOSISI POHON DI PLOT PERMANEN HUTAN ALAM PINOLOSIAN KABUPATEN BOLAANG MONGONDOW SELATAN - Darsan Umawaitina; Fabiola B. Saroinsong; Wawan Nurmawan (COCOS, 2018)
ABSRACT The purpose of this study was to analyze the structure and composition of trees in the permanent plots of the Pinosian Natural Forest, South Bolaang Mongondow Regency. This research will be carried out in September-October 2018. Data is collected using the transect method. There are 5 transects within 500 m, the five transects are permanent transects that have been made by management (PT. Kawanua Kahuripan Pantera). In each transect, there are 5 observation plots measuring 20x20 m2. The distance between observation plots in the transect is 100 m. Observations were made on each individual tree in the observation plot, namely: identification of species and diameter measurements for individual trees that have a diameter of ≥20 cm. There are 25 tree species from 20 families, species with the highest INP are Palaquium gutta (40.52%), Magnolia obovata (18.61%), Macaranga sp (15.56%), and Pometia pinnata (13.39%). The tree structure shows that the distribution of the highest diameter class is the diameter class ≥40-50 cm (26%) and ≥50-60 cm (25%). Keywords: structure and composition, natural forest, Pinosian